The Development of the Entrepreneurial Spirit Index: An Application of the Entrepreneurial Cognition Approach - Suchart Tripopsakul; Tartat Mokkhamakkul; Wilert Puriwat (Ital Publication, 2022)
Entrepreneurship has been recognized as one of the crucial mechanisms for a nation’s sustainable economic development. Entrepreneurship is a key engine that propels economic growth and employment opportunity creation. The purposes of this study are: (1) to develop and validate the Thailand Entrepreneurial Spirit Index (THESI) in combination with multidimensional entrepreneurial cognition scales, by examining the attitudes, motivations, and ambitions of individuals starting businesses; and (2) to investigate the impacts of a multitude of perception factors and demographic factors on entrepreneurial intent. Based on 1,180 samples of the Thai population collected via a telephone survey in 2021, the results of tetrachoric correlation and factor analysis showed that the THESI index can be formulated and explained by six variables: entrepreneurial intent (b = 0.690), opportunity recognition (b = 0.711), self-skill perception (b = 0.935), entrepreneurial networking (b = 0.743), perceived ease of doing business (b = 0.470), and fear of failure (b = –0.118). The results of binary logistic regression analysis revealed that opportunity recognition, self-skill perception, entrepreneurial networking, perceived ease of doing business, and fear of failure have significant effects on entrepreneurial intent. Interestingly, females are 36.6% less likely than males to declare entrepreneurial intent. Older adults over age 61 indicate significantly lower entrepreneurial intent, at 76.8%, compared with younger people 18 to 30 years old. The amount of formal education a person possesses has a considerable negative impact on their desire to start a business. The group of respondents holding above a bachelor’s degree sample shows 22.0% lower entrepreneurial intent than the group holding a bachelor’s degree or below. Our research is among the few pioneering efforts to provide an improved idea of how to quantify an unlikely, non-measurable concept: the entrepreneurial spirit. This novel THESI index will help national entrepreneurial policymakers evaluate the degrees of entrepreneurship at a societal level. The value of this THESI index relies upon applied simpler metrics to portray a key issue related to the interpretation of entrepreneurship at the societal level. Doi: 10.28991/ESJ-2022-06-03-05 Full Text: PDF